The analysis of factors determining low probability of organizing and existence of illegal armed formations on the present-day Ukraine territory - Batsamut V. М.; Babkov, Yu. P. (Honor and Law, 2019)
Major factors that cause low probability of realization of one of the threats to the national security of Ukraine – an attempt of organizing and existing of illegal armed formations on the present-day Ukraine territory are considered and analysed Forms of actual threats to the national security of Ukraine in internal political sphere are determined.